On Strategic Ignorance of Environmental Harm and Social Norms - Linda Thunström; Klaas van 't Veld; Jason F. Shogren; Jonas Nordström (Lund University, School of Economics and Management, Department of Economics, 2013)
Are people strategically ignorant of the negative externalities their activities cause the environment? Herein we examine if people avoid costless information on those externalities and use ignorance as an excuse to reduce pro-environmental behavior. We develop a theoretical framework in which people feel guilt from causing harm to the environment (e.g., emitting carbon dioxide) and from deviating from the social norm for pro-environmental behavior (e.g., offsetting carbon emissions). Our model predicts that people may benefit from avoiding information on their harm to the environment, and that they use ignorance as an excuse to engage in less pro-environmental behavior. It also predicts that the cost of ignorance increases if people can learn about the social norm from the information. We test the model predictions empirically with an experiment that involves an imaginary long- distance flight and an option to buy offsets for the flight's carbon footprint. More than half (53 percent) of the subjects choose to ignore information on the carbon footprint alone before deciding their offset purchase, but ignorance significantly decreases (to 29 percent) when the information additionally reveals the social norm, namely the share of air travelers who buy carbon offsets. We find evidence that some people use ignorance as an excuse to reduce pro-environmental behavior— ignorance significantly decreases the probability of buying carbon offsets.
Keywords: D03; D81; D83; 330; Behavioral; Decision Making; Externality; Ignorance; Social norms